2017
DOI: 10.1039/c6sm02335e
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of collective dynamical chirality for achiral active particles

Abstract: Emergence of collective dynamical chirality (CDC) at mesoscopic scales plays a key role in many formation processes of chiral structures in nature, which may also provide possible routines for people to fabricate complex chiral architectures. So far, most of reported CDCs are found in systems of active objects with individual structure chirality or/and dynamical chirality, and whether CDC can arise from simple and achiral units is still an attractive mystery. Here, we report a spontaneous formation of CDC in a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 47 publications
1
25
1
Order By: Relevance
“…motion, spatial confinement, and hydrodynamic interaction. 124 A different conclusion arose when Bartolo and coworkers 82 considered vortices of motile particles with velocity-aligning interactions (Fig. 8B).…”
Section: Present Research Status (Collective Dynamic States)mentioning
confidence: 98%
See 1 more Smart Citation
“…motion, spatial confinement, and hydrodynamic interaction. 124 A different conclusion arose when Bartolo and coworkers 82 considered vortices of motile particles with velocity-aligning interactions (Fig. 8B).…”
Section: Present Research Status (Collective Dynamic States)mentioning
confidence: 98%
“…Hou and coworkers constructed a continuum theory to describe vortical motion of motile populations constrained by geometrical boundaries. 124 They concluded that collective dynamic chirality arises spontaneously in systems of both dynamically and structurally achiral particles, controlled physically by the active force and the resistance time over which particles maintain their motion. Intriguingly, chirality oscillation was found to be possible (Fig.…”
Section: Present Research Status (Collective Dynamic States)mentioning
confidence: 99%
“…We considered ABPs moving in a two‐dimensional rectangular space with long‐range HI. [ 67 ] In simulations, we used the stochastic lattice Boltzmann method to address the long‐ range HI, [ 68 ] and rewrote the orientation equation as θ̇i=() 1/τ[] arg() true r¨iθi+ζi. [ 69‐71 ] Herein, arg() true r¨i denotes the angle of the total force vector, the resistance time τ measures the ability of ABPs resisting the external steering.…”
Section: From Individual To Collectivementioning
confidence: 99%
“…(Figure adapted with permissions from Ref. 67 and 73. Copyright 2017 and 2019 The Royal Society of Chemist.…”
Section: From Individual To Collectivementioning
confidence: 99%
“…Activity can also induce self-organized flow states [13]. In confining channels, an extensile active stress induced instability to bend perturbations leads to selfsustained spontaneous flows [14][15][16][17][18] and spontaneous circulations [19][20][21][22][23][24][25][26][27] when the characteristic activity length scale act is comparable to the confinement size L. Vortex lattices arise when the characteristic length scale matches the confinement, which can be due to an array of obstacles or cavities [28][29][30][31][32][33][34], bound to spherical surfaces [35], or channel confinement [36][37][38][39]. Local circulations arise because act represents the characteristic vorticity length scale [40], associated with a peak in the enstrophy distribution [41][42][43][44], and a lattice of vortices represents stressfree solutions that lie at the interface of the stable and unstable modes in minimal continuum models of active fluids [45].…”
mentioning
confidence: 99%